Comment la fiction contemporaine travaille ses lecteurs - Nancy Murzilli (Contextes)
Thinking about the effects of fiction on individuals and society means to consider it from a pragmatic point of view as something that operates within and from the world. This implies to analyse the way in which contemporary writers work on the fiction and readers are worked on by it. What can literature do in front of neoliberalist storytelling practices whose objective is to invent an "actionable" concept-solution, effective in terms of like, follow and sale ? Literature can recognize its instrumental value, share its confidence within the fiction’s power to act on the world, and then use it as a lever for other possible purposes. This essay deals with the way in which fictions can work as inquiries on practical life and forms of individual and collective life, in the way that thought experiments fulfill their heuristic function.